Strategi Badan Narkotika Nasional (BNN) Dalam Mencegah Dan Memberantas Peredaran Narkoba Di Kota Tanjungbalai - Jexcen Simamora; R. Sally Marisa Sihombing (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
The Tanjungbalai City National Narcotics Agency is a government agency that has the authority to take action to prevent and eradicate drug trafficking in the Tanjungbalai City area. Through this research it can be seen that the Tanjungbalai BNN with all its resources and efforts has carried out drug prevention by using prevention strategies through programs that are arranged systematically as in the results of the BNN Strategic Plan in which there are concrete activities of the programs to be implemented in an effort to prevention and eradication. A supporting factor in the National Narcotics Agency's strategy in preventing eradication is the support from the government and other government agencies as well as some members of the public who care about this prevention. Then what becomes the inhibiting factor in this prevention is the drug problem which is increasingly complex and requires a large amount of money to prevent it. Besides that, it is necessary to increase the number of juridical and physical personnel because human resources are important actors in a policy. However, the Tanjungbalai City BNN continues to carry out its duties to the maximum extent possible to eradicate the perpetrators of narcotics crimes.